English for Garment Technology and Fashion design – Book 3 - Khoa Ngoại ngữ - Trường Đại học Công nghiệp Hà Nội
I have recycled old papers! ,What happened?What will it be like?,First…and then…!,How about?,How was it produced?,I like guys who are creative!,I don’t agree with you!